Higher oil prices : worldwide financial implications - Lea, Sperry; British-North American Committee (Washington, D.C. : British-North American Committee, 1975)
This book is on the implication of high oil prices in the world.
Includes bibliographical references.
oo 15/04/2019
Loans
Keywords: Petroleum products; Petroleum industry and trade; International finance